Nutrition Knowledge and Satisfaction Levels of Postbariatric Surgery Adults in the United Arab Emirates: A Pilot Study - Souheir Alia; Habiba I. Ali; Taoufik Zoubeidi; Mariam Ahmed (Journal of Nutrition and Metabolism)
Research assessing the nutrition knowledge of postbariatric surgery patients is limited, although this category of patients is predisposed to malnutrition. In this pilot study, we explored postbariatric nutrition knowledge, satisfaction levels with dietitian nutrition counseling, and decision to undergo bariatric surgery of 83 patients who attended a postbariatric outpatient nutrition clinic in Dubai, United Arab Emirates (UAE). A cross-sectional design involving gender-stratified random sampling method was used to recruit 83 postbariatric surgery participants. A self-administered questionnaire was employed to collect information about nutrition knowledge related to dietary recommendations after bariatric surgery as well as participant views on dietitian nutrition counseling, their decision to undergo bariatric surgery, and nutrition-related complications experienced after the surgery. The mean (SD) knowledge score of postbariatric diet was 9.7 (2.05) out of a maximum possible score of 14. The majority of the participants (78.3%) correctly identified which foods are recommended during the first stage of the postbariatric surgery diet, and more than 90% knew about the importance of high-protein supplements after bariatric surgery. Female participants had significantly higher mean knowledge score compared to males (p=0.02). Although nearly 80% of the participants reported regular follow-up with their dietitian, only 10.8% reported high adherence to the dietitian’s instructions. Moreover, more than two-thirds of the participants (71.1%) rated dietary advice provided by dietitians as vague. The most common complication experienced by the participants after bariatric surgery was nausea (61.4%). Furthermore, the majority of the participants (83.4%) found their daily and leisure activities to be more enjoyable after bariatric surgery. Ways of improving the quality of information delivery by dietitians should be explored to enhance patient comprehension and adherence to postbariatric surgery diet recommendations. Future research involving a larger and more representative sample to extend our findings are needed.